2021
DOI: 10.1177/00220027211042681
|View full text |Cite
|
Sign up to set email alerts
|

Sanctioning the Homeland: Diasporas’ Influence on American Economic Sanctions Policy

Abstract: Why do some immigrant groups succeed in influencing the U.S. government to impose economic sanctions on their former dictators, while others do not? This paper begins by noting that the president is the pivotal player in sanctions policy and that presidents cater to voters in swing states. Therefore, a diaspora’s proportion of the swing-state electorate should determine whether the American government imposes sanctions on their former homeland. Considering dictatorships from 1946 to 2005, this paper finds that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…A large Russian diaspora in MEPs' home countries is associated with increased support for financial aid and trade with Ukraine, across all models and with conventional levels of significance. Following Kustra (2020), it is possible that a large share of Russian immigrants in EU member states are not supportive of their kin-state's preferred policy, and may be willing to punish Russia through policies that are oppose its interests. Similarly, Eastern European MEPs are more likely to support EU-Ukraine cooperation and not follow the pro-Russian policy.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large Russian diaspora in MEPs' home countries is associated with increased support for financial aid and trade with Ukraine, across all models and with conventional levels of significance. Following Kustra (2020), it is possible that a large share of Russian immigrants in EU member states are not supportive of their kin-state's preferred policy, and may be willing to punish Russia through policies that are oppose its interests. Similarly, Eastern European MEPs are more likely to support EU-Ukraine cooperation and not follow the pro-Russian policy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The role of immigrant groups and diasporas in policy-making has been studied for decades in international relations (Bermeo and Leblang, 2015). Immigrant groups tend to lobby host country governments on policies towards to their kin-state (Bermeo and Leblang, 2015: 627), although these policies may range between support for kin-state governments and punishing the kin-state through economic sanctions (Kustra, 2020).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…In this article, I revisit the diversionary theory, adapting it to the use of economic sanctions by US presidents. For some time now, scholars have looked into the influence of domestic conditions on the initiation of sanctions (Drury, 2001(Drury, , 2005Kustra, 2022;Tama, 2020). They provide us with mixed findings on the link between the domestic economy and sanctions onset: While early studies showed that higher levels of unemployment are associated with a greater likelihood of sanctions imposition (Drury, 2001), later research pointed in the opposite direction, demonstrating that a weak economy constrains the president from using sanctions (Drury, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of this article is to expand our understanding of sanctioning behavior while maintaining the simple, two-player setup. Kustra (2022) considers how domestic political advocacy by immigrant groups affects sanctions and finds that the president caters to diasporas when they form an important voting block in swing states.…”
Section: Introductionmentioning
confidence: 99%